Arboreal frogs, tank bromeliads and disturbed seasonal tropical forest - Galindo-Leal, Carlos; Cendo-Vazquez, J. Rogelio; Calderon, Rene; Augustine, Justine (Contemporary Herpetology, 2003)
We investigated the relationship between arboreal frogs, tank bromeliads and landscape transformation in tropical forests of southeastern Campeche, Mexico. We surveyed frogs in six distinct habitats: slash and burn agriculture, seasonally flooded forest (bajo), aquatic habitats (lagoons and small ponds), second growth upland forest, primary forest and creek habitat using both systematic and non-systematic surveys. The highest species richness of frogs was documented in primary forest and small ponds. In contrast, no frogs were recorded in second growth forest. Similarly, tank bromeliads (Aechmea bracteata) were completely absent from early successional stages and were almost twice as abundant in seasonally flooded forest as in upland forest. The vertical distribution of A. bracteata differed between forest types, and they significantly more abundant in larger diameter trees. We examined 60 tank bromeliads during the peak of the dry season to test their use as refugia by frogs. Approximately 27% of tank bromeliads sampled had arboreal frogs belonging to three species, but 9 species have been recorded as occasional users of bromeliads in the region. There were significantly more frogs on large than on medium-sized bromeliads, and frogs were more abundant on bromeliads higher on host trees, particularly those above 3 m in height. Our results suggest that the loss of tank bromeliads from drier and less structurally complex habitats created by slash and burn agriculture and selective logging results in loss of refugia for arboreal frogs in this seasonal tropical forest. We suggest that Aechmea bracteata be a keystone species in seasonal tropical forest.